Assessment Instruments for Critical Thinking Ability in Basic Work Lessons of Industrial Engineering Class - Jumhur, Aam Amaningsih; Mahir, Imam; Avianti, Ratu Amilia; Susilawati, Risa (Journal of Education Reseach and Evaluation, 2021)
The quality of education for the improvement is inseparable from the application of appropriate assessments to measure the final result and a quality measuring instrument is needed so that the assessment instruments used by educational units must meet the requirements, one of which has evidence of empirical validation. This research was conducted to produce a valid and reliable assessment instrument for critical thinking skill. The research method used is Research and Development, using methods.4D development, namely 1) observation and study of literature, 2) expert validation test, 3) testing for students, 4) ready-to-use product. The results of this study obtained. the result of that type. research instrument. which is developed feasible. used with analysis indicators, interpretation, inference, evaluation, explanation, Induction, deduction. The assessment instrument developed was PG (Multiple Choice). The difficulty test shows that of the 40 questions made have a difficulty level of 0.27 to 0.44, which is in the difficult and moderate criteria, on the test results 5 questions are stated as good, 17 questions are stated as sufficient, and 18 questions are said to be bad. The instrument for assessing critical thinking skills in basic mechanical engineering subjects was declared valid for 30 out of the 40 questions made and the reliability value was 0.82, then it was declared as realistic. Conclusion, the instrument for assessing critical thinking skills in the basic engineering work course is feasible.